2009
DOI: 10.3329/jsr.v1i3.2595
|View full text |Cite
|
Sign up to set email alerts
|

Nematic van der Waals Free-energy

Abstract: We develop the calculation of free energy in a nematic phase for a model of spherical particles with the long-range anisotropic interaction from the van der Waals theory. We map the gas-liquid equilibrium, which is coupled to a first-order isotropic-nematic transition. We discus how the topology of the phase diagrams changes upon varying the strengths of the isotropic and nematic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
(46 reference statements)
0
6
1
Order By: Relevance
“…The N' branch is the unphysical branch because ηf is a concave function of η . The N branch, however, is the physical branch because ηf is a convex function of η (see [32] for more details). In our previous study [32], we have shown that the nematic phase can only occur for q larger than 1.51 or 2 t φ γ γ * = larger than 2.24.…”
Section: The Free Energymentioning
confidence: 99%
See 4 more Smart Citations
“…The N' branch is the unphysical branch because ηf is a concave function of η . The N branch, however, is the physical branch because ηf is a convex function of η (see [32] for more details). In our previous study [32], we have shown that the nematic phase can only occur for q larger than 1.51 or 2 t φ γ γ * = larger than 2.24.…”
Section: The Free Energymentioning
confidence: 99%
“…The N branch, however, is the physical branch because ηf is a convex function of η (see [32] for more details). In our previous study [32], we have shown that the nematic phase can only occur for q larger than 1.51 or 2 t φ γ γ * = larger than 2.24. In other words, the isotropic-nematic transition is always of the first-order type because the order parameter q has to jump from q=0 to 1.51. q ≥ In the following we will give the phase diagram for the fluid phases (both isotropic and nematic), solid phases, and finally we present the complete phase diagram where both fluid and solid phases are present.…”
Section: The Free Energymentioning
confidence: 99%
See 3 more Smart Citations